Identification of the receptor for erythropoietin by cross-linking to Friend virus-infected erythroid cells. - Sawyer, S T (1987)
Erythropoietin (Epo) is a glycoprotein hormone that regulates erythroid development and interacts with surface receptors on developing erythroid cells. In this laboratory, a cell system with a relatively pure population of erythroid cells that respond to Epo has been developed. Immature erythroid cells are obtained from the spleens of mice infected with the anemia strain of Friend virus. The binding of 125I-labeled Epo (125I-Epo) to plasma membranes from these cells was studied in this investigation. 125I-Epo binding reached equilibrium within 20 min at 37 degrees C. Twenty percent of the receptors bound 125I-Epo with a Kd of 0.08 X 10(-9) M, while the remaining receptors bound the hormone with a Kd of 0.6 X 10(-9) M. In this study, a receptor for Epo was identified by cross-linking 125I-Epo to the receptor in intact cells and plasma membrane preparations using disuccinimidyl suberate. Polyacrylamide gel electrophoresis revealed two labeled bands of 100 and 85 kDa. The 85-kDa band was more heavily labeled (65%) than the 100-kDa band. Both bands were equally decreased when increasing amounts of unlabeled Epo were included in the binding mixture, indicating a specific interaction of 125I-Epo with the receptor.